Public Access to Privately Owned Land in Maine - Acheson, James (Maine Policy Review, 2006)
In Maine, people have long used private land for recreation. James Acheson points out that this “open land” tradition—unique in the nation—has huge economic implications, especially for the state’s tourism industry. In recent years, there has been a substantial increase in land posting, largely in response to abuses by the public. Although a number of different kinds of institutions have arisen to allow continued public access to private land, Acheson suggests that more needs to be done if Maine’s “open land” tradition is to be maintained